Assistance of Children in Conflict with the Law during the Investigation Process at Medan Police - Dewi Ervina Suryani; Cynthia Cynthia; Kezia Carolina Tampubolon; Putri Damayanti Sihombing (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to find out how to assist children who are confronted with the law during investigations at the Medan Polrestabes in resolving child cases. The resolution of the problem of juvenile delinquency can be carried out peacefully outside the court, based on the principles of solidarity and publicity. Restorative Justice emphasizes the principles of togetherness and openness so that assisting children who are confronted with the law is suitable for using restorative justice. Compared to punishment, reconciliation is more beneficial for the physical and mental development of children. This research method uses empirical legal research methods, namely field research, which is to conduct research systematically and methodically to reveal the data needed for research from a location or field. While the data collection techniques used are interviews, documentation studies. And the data analysis used is data analysis that seeks to provide a clear and concrete picture of the objects discussed quantitatively and presented descriptively. The results of this research can be concluded that assistance to children in conflict with the law is carried out without causing fear to children and not putting pressure on children.